WZMOCNIENIE REGULACJI NA HURTOWYCH RYNKACH ENERGII ELEKTRYCZNEJ W ŚWIETLE ROZPORZĄDZENIA UE NR 1227/2011 (REMIT) - Radziński, Mateusz (Kwartalnik Prawa Publicznego, 2016)
REMIT Regulation has been designed to effectively detect abuses on wholesale energy markets, such as the misuse of inside information, manipulation and any attempts to manipulate the energy market. In order to strengthen the regulation in this area REMIT requires close cooperation between ACER and national regulatory authorities and introduces tools designed to prevent market abuses, which should be sanctioned. The aim of this article is to discuss the solutions adopted on the basis of REMIT, as well as present the proposed solutions in the context of the amendment to the Energy Law.